1998
DOI: 10.1001/jama.279.16.1282
|View full text |Cite
|
Sign up to set email alerts
|

Indications, Outcomes, and Provider Volumes for Carotid Endarterectomy

Abstract: Context.-While trials have demonstrated that carotid endarterectomy is superior to best medical therapy, most recently among asymptomatic patients, uses and outcomes of the procedure in more representative settings have not been established. Objectives.-To profile the use and outcomes of carotid endarterectomy in a representative sample of Ohio's Medicare beneficiaries and to examine the relationships between provider-specific procedural volumes and patient outcomes. Design.-Retrospective cohort using Medicare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
71
0
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 216 publications
(76 citation statements)
references
References 32 publications
4
71
0
1
Order By: Relevance
“…This mortality rate is lower than the 0.7% mortality rate reported in Pennsylvania, 18 and the adverse event rate is lower than the 2.7% adverse event rate reported by Maxwell et al 19 in North Carolina, the 4.0% rate reported by Kresowik et al 20 in Iowa, the multistate study by Kresowik et al, 21 or the 4.7% 30-day rate reported by Cebul et al 14 in Ohio. However, the Kresowik et al 20 and Cebul et al 14 studies were limited to Medicare patients who clearly have higher adverse event rates because of their age.…”
Section: Discussionmentioning
confidence: 48%
“…This mortality rate is lower than the 0.7% mortality rate reported in Pennsylvania, 18 and the adverse event rate is lower than the 2.7% adverse event rate reported by Maxwell et al 19 in North Carolina, the 4.0% rate reported by Kresowik et al 20 in Iowa, the multistate study by Kresowik et al, 21 or the 4.7% 30-day rate reported by Cebul et al 14 in Ohio. However, the Kresowik et al 20 and Cebul et al 14 studies were limited to Medicare patients who clearly have higher adverse event rates because of their age.…”
Section: Discussionmentioning
confidence: 48%
“…[1][2][3][4][5][6][7][8][9] Although studies have refuted this assertion, 5 the majority seems to accept the relationship. Overall, this understanding has also been reached in the field of transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, research has shown an association between low case volume and poor outcomes in a multitude of surgical procedures, [1][2][3][4][5] such as hysterectomy, 6 pancreatectomy, 5,7 esophagectomy, 5 pelvic exenteration, 5 and coronary artery bypass surgery. 2,8,9 Studies have also shown this relationship in several pediatric procedures of varying complexity, such as cardiac surgery, 10,11 pyloromyotomy, 12 appendectomy, 13,14 and inguinal hernia repairs.…”
Section: What This Study Addsmentioning
confidence: 99%
“…[30][31][32][33][34][35][36][37][38][39][40][41][42][43] In general, asymptomatic patients with carotid artery stenosis are treated more conservatively in Europe than in the United States. Asymptomatic patients with carotid artery stenosis comprise 11-52% and 37-92% of all patients operated for carotid artery stenosis in Europe and the United States, respectively.…”
Section: Discussionmentioning
confidence: 99%